2000
DOI: 10.1177/1354067x0062003
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic, Cultural and Cognitive Capacities of Bonobos(Pan Paniscus)

Abstract: When human cultures merge, each takes on characteristics of the other and a completely new culture may emerge. Can a similar kind of phenomenon occur when the ways of being, doing, thinking, speaking and acting meld between two closely related hominid species, like Pan and Homo? We point to a new kind of group process, termed a Pan/Homo culture, and characterized by changes in the behavior of each species. A common emic perspective has developed between members of different species as they have come to share a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…In 2000, William Fields and Savage-Rumbaugh developed a novel, cultural explanation of why Kanzi acquired language. They suggested that what distinguished the work with Kanzi from the work with Nim was that Savage-Rumbaugh allowed a bi-species culture to develop between apes and humans: a Pan/Homo culture (Savage-Rumbaugh and Fields, 2000). This explanation is further developed in Segerdahl et al (2005).…”
Section: Farms As Local Human/animal Culturesmentioning
confidence: 90%
“…In 2000, William Fields and Savage-Rumbaugh developed a novel, cultural explanation of why Kanzi acquired language. They suggested that what distinguished the work with Kanzi from the work with Nim was that Savage-Rumbaugh allowed a bi-species culture to develop between apes and humans: a Pan/Homo culture (Savage-Rumbaugh and Fields, 2000). This explanation is further developed in Segerdahl et al (2005).…”
Section: Farms As Local Human/animal Culturesmentioning
confidence: 90%
“…And on grounds of genetic and behavioural similarity, we would certainly expect for nonhuman primates to manifest intersubjectivity and consciousness. Indeed, some enculturated nonhuman primates could be argued to have mastered a rudimentary language in the sense that Wittgenstein means and have even been reared to different extents with human caregivers, and thereby afforded the opportunity to acquire some experience in this complicated form of life (see Savage-Rumbaugh & Fields 2000;. Taking his cue from the talking lions, Gill (1997: 26) argues that such chimpanzees "do speak and we do understand them because, at least to a significant extent, we share a common 'form of life, ' grounded as it is in gestural, reciprocal, and task-oriented embodiment. "…”
Section: Wittgenstein Intersubjectivity and Consciousnessmentioning
confidence: 99%
“…In particular, it has been established that, with training, apes can learn vast sets of visual symbols and can combine these productively (e.g., Savage-Rumbaugh et al, 1993; Savage-Rumbaugh and Lewin, 1996; Lyn and Savage-Rumbaugh, 2000; Savage-Rumbaugh and Fields, 2000). Follow-up studies have documented that chimpanzees and bonobos raised in symbol-rich environments can develop a vocabulary and utterance complexity similar to those of 3 year-old children (Lieberman, 1984, chapter 10; Gardner and Gardner, 1985, 1969; Pedersen, 2012).…”
Section: Introductionmentioning
confidence: 99%